Effectively optimizing esports performance through movement science principles - Iwatsuki, T.; Hagiwara, G.; Dugan, M. E. (International Journal of Sports Science & Coaching, 2022)
Esports has been the fastest-growing industry around the globe, as the number of games and prize earnings are dramatically increasing. Esports is defined as competitive sport video gaming; more individuals are beginning to pursue this as a profession. Just like the University of California, Irvine, which offers a program to enhance esports skills and performance, the number of such institutions are expected to increase in this century; yet, research on how individuals effectively optimize esports performance is lacking. Specifically, how teachers or instructors lead players to enhance their esports performance has not been extensively discussed. The review article aimed to introduce two motivational factors that, from the existing movement science and psychological literature, have consistently been demonstrated to enhance motor skills (physical tasks): enhanced expectancies for success and autonomy support. Practical implications for enhancing esports performance and future direction were also discussed.